Changes in the diet and feeding of the hake Merluccius merluccius at the shelf-break of the Balearic Islands: Influence of the mesopelagic-boundary community - Cartes, Joan Enric; Hidalgo, Manuel; Papiol, Vanesa; Massutí, Enric; Moranta, Joan (Deep Sea Research Part I: Oceanographic Research Papers, 2009)
22 pages, 10 figures, 3 tables Short spatio–temporal variations in the feeding intensity and the diet of the European hake, Merluccius merluccius, together with the abundance of their potential prey were studied between August 2003 and June 2004 at two locations, northwest (Sóller) and south (Cabrera), off the island of Mallorca (Balearic Islands, Western Mediterranean) at depths between 150 and 750 m. The two areas present different oceanographic conditions. Hake was mainly distributed along the shelf-slope break and the upper slope (between 166 and 350 m) where recruits (TL<18 cm) were dominant. The hake's diet varied as a function of size. Recruits fed mainly on micronektonic prey, and the diet was influenced primarily by seasonality, with two dietary patterns (identified by MDS analyses) corresponding to August–September 2003 (summer) and to November 2003/February–April 2004 (autumn–winter). The summer pattern was consistent with a thermally stratified water column, while November and April were consistent with homogenized temperature and salinity throughout all the water column. The main prey of recruits were the euphausiid Meganyctiphanes norvegica and the midwater fish Maurolicus muelleri in autumn–winter and myctophids (mainly Ceratoscopelus maderensis) in summer. In contrast to recruits, the geographic factor (NW vs. S) was the main factor influencing the diets of post-recruits (TL between 18 and 21.9 cm) and adults (TL ≥ 22 cm). Hake recruits (and to a lesser extent post-recruits) and their preferred prey occupied different depth ranges during daylight periods. Meganyctiphanes norvegica and Ceratoscopelus maderensis were, for instance, distributed as much as 500 m deeper than hake that had eaten them. All these trends were especially obvious at NW, an area with a more abrupt slope and with a greater influence by northern winter intermediate water (WIW) inflow in early spring than the S area. These factors probably enhanced micronekton aggregation in April, when feeding intensity (stomach fullness) ...